Study of nuclear morphometry in the cytologic evaluation of thyroid neoplasms - Thomas, Joyce; Chhadi, Tulsi Shyam; Chhadi, Hirkani (Journal of Pathology of Nepal, 2023)
Background: Nuclear morphometry is purported to allow better differentiation between various thyroid lesions beyond what is offered by conventional cytology. The present study was conducted to evaluate the nuclear morphometric parameters in fine needle aspirates of thyroid neoplasms and to study their role in differentiating benign and malignant thyroid neoplasms.Materials and Methods: Nuclear morphometric parameters of all the patients presenting with thyroid swelling and undergoing fine needle aspiration cytology (FNAC) and belonging to Category III, IV, V, and VI of the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) were studied.Results: Out of a total of 60 cases, a maximum was noted from category IV which is follicular neoplasm or suspicious for follicular neoplasm. The sensitivity of FNAC for the diagnosis of thyroid lesions in the present study was observed at 87.71%. The nuclear morphometry parameters – short axis diameter, long axis diameter, nuclear area, and perimeter showed significant differences between benign and malignant lesions (p-value